Evaluación del ángulo de contacto en formulaciones adhesivas a base de lignina despolimerizada sobre madera - Romero García, Erandi (Universidad Michoacana de San Nicolás de Hidalgo, 2019)
Considering that wood is a lignocellulosic and porous material, the penetration of the liquid through the pores is an important factor in the design of adhesive formulations. Adhesive wetting on a wood surface includes contact angle formation, dispersion cause the contact angle to change as a function of time. The objective of this work is to link the adhesive capacity of the formulations (lignin-phenol-formaldehyde) by varying the contact angle, which indirectly provides us with the affinity of the adhesive with the material, so that if the drop of the adhesive extends into a thin film with a zero contact angle, leaves no doubt that the adhesive has wetted the solid well, and is in close contact with it, on the contrary if the drop does not extend on the surface, or ever retracts by raising the angle, will indicate the little or no affinity of this adhesive with the material. The adhesive, as a binding element, is an integral part of our time. The growing need to have materials assembly technologies, in this case wood, leads to study the behavior of the adhesion to generate these joints, more than traditional techniques such as reverting or screwing, so it requires the evaluation of behavior of the contact angle of wood adhesive formulations based on depolymerized lignin on wooden surfaces.

Considerando que la madera está constituida generalmente por: carbohidratos (celulosa, hemicelulosas), lignina y extraíbles, por lo que se puede identificar como lignocelulósica y porosa. La penetración del líquido por sus poros es un factor importante en el depósito de formulaciones adhesivas, las cuales son evaluadas por medio del ángulo de contacto en este trabajo. La humectación adhesiva en una superficie de madera implica: la formación del ángulo de contacto, la dispersión y la penetración, tanto la penetración como la dispersión provocan que el ángulo de contacto cambie en función del tiempo. El objetivo de este trabajo es vincular la capacidad adhesiva de las formulaciones (lignina-fenol-formaldehído) mediante la variación del ángulo de contacto, el cual nos proporciona indirectamente la afinidad del adhesivo con el material. La creciente necesidad de contar con tecnologías de ensamblado de materiales, en este caso de maderas, conlleva a estudiar el comportamiento de la adhesión para generar esas uniones, más que las técnicas tradicionales como remachado o atornillado, por lo que se requiere la evaluación del ángulo de contacto en diseño de formulaciones adhesivas para superficies de madera.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2019-2024; Ángulo de contacto; Humectabilidad; Adhesión; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1474